2000
DOI: 10.1046/j.1469-8137.2000.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of ectomycorrhizas synthesized on Douglas fir by Rhizopogon spp. and the hypogeous relative Truncocolumella citrina

Abstract: The morphology and anatomy of ectomycorrhizas of Rhizopogon parksii, Rhizopogon vinicolor and Rhizopogon subcaerulescens, and a hypogeous relative, Truncocolumella citrina, synthesized on Douglas fir in glasshouse conditions using spore slurries as inoculum, are described and compared. Mycorrhizas formed with R. parksii and R. vinicolor did not exhibit their characteristic subtuberculate morphology in these tests, but rather had a pinnate form. All species had diagnostic features of ectomycorrhizas : a well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…These features are in agreement with the study conducted by Mohan et al [88] with Rhizopogon luteolus and Pinus patula; Sulzbacher et al [89] with Rhizopogon verii and Pinus sylvestris; Raidl et al [90] with Rhizopogon melanogastroides + Pinus mugo; Raidl and Agerer [91] with Rhizopogon roseolus + P. sylvestris; Jakucs et al [92] with R. vulgaris + P. nigra; Singh [29] and Thakur [25] observed racemose to coralloid branching in R. himalayensis + C. deodara association. Species within the genus Rhizopogon are known for their abundant formation of specialized structures called rhizomorphs, believed to have a significant role in water uptake [93]. In accordance with the findings of Mohan et al [88] concerning the R. luteolus + Pinus patula association, the extraradicle hyphae were observed to be hyaline, septate, unbranched, and lacking clamp connections.…”
Section: Discussionsupporting
confidence: 69%
“…These features are in agreement with the study conducted by Mohan et al [88] with Rhizopogon luteolus and Pinus patula; Sulzbacher et al [89] with Rhizopogon verii and Pinus sylvestris; Raidl et al [90] with Rhizopogon melanogastroides + Pinus mugo; Raidl and Agerer [91] with Rhizopogon roseolus + P. sylvestris; Jakucs et al [92] with R. vulgaris + P. nigra; Singh [29] and Thakur [25] observed racemose to coralloid branching in R. himalayensis + C. deodara association. Species within the genus Rhizopogon are known for their abundant formation of specialized structures called rhizomorphs, believed to have a significant role in water uptake [93]. In accordance with the findings of Mohan et al [88] concerning the R. luteolus + Pinus patula association, the extraradicle hyphae were observed to be hyaline, septate, unbranched, and lacking clamp connections.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, root morphology in ectomycorrhiza of R. himalayensis and C. deodara roots was found to be analogous to the observations of Singh (1992), who noticed racemose to coralloid branching in this association. Similar branching was illustrated in various mycorrhizal associations of Rhizopogon species, for instance, coralloid in R. vulgaris-Pinus contorta Agerer et al, 1996); monopodial to dichotomous in R. subcaerulescens -Pseudotsuga menziesii (Massicotte et al, 1999); pinnate in R. vinicolor and R. parksii with P. menziesii (Massicotte, et al, 2000). Although, different root morphologies have also been reported in other Rhizopogon species, i.e.…”
Section: Discussionmentioning
confidence: 53%
“…In both systems, hyphal contact induced significant modifications in root hair structure, causing deformation and subsequent incorporation of root hair in the fungal mantle. On the contrary, in Betula alleghaniensis-Laccaria bicolor (Massicotte et al, 1989) and Pseudotsuga menziesii-R. parksii mycor-rhiza (Massicotte, 2000), hyphal contact caused wall thickening in root hair, preventing the collapse of root hair. Colour had also been found as an important feature while describing ectomycorrhizal morphology (Zak, 1973;Agerer et al, 1986) and which also showed variations with the advancement of age of mycorrhiza (Haug and Oberwinkler, 1987).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Root hairs respond by developing thickened cell walls as the interaction progresses (Massicotte et al 2000). In this study, hyphal clusters covered root hair zones on early colonizing lateral roots and the root hairs bent and collapsed in contact with hyphae, which adhere closely to mucilage materials and were embedded in the epidermis.…”
Section: Discussionmentioning
confidence: 65%